Block shear strength in thin-walled lean duplex stainless steel fillet welded connection with base metal fracture. (January 2022) - Cho, YongHyun; Kim, TaeSoo; Kim, Dong-Keon; Hwang, BoKyung; Yoo, Jung-Han
Abstract: This paper investigates the accuracy of different design equations given in design specifications and literatures in determining the block shear strength of the lean duplex stainless steel fillet welded connections with base metal fracture. It points out the problem inherent in the block shear provision specified in the North American cold-formed design specification, which does not consider shear strain hardening. The previous test results have found that full shear strain hardening can be assumed for the carbon steel and ferritic stainless steel welded connections, but not applicable to the thin-walled lean duplex stainless steel welded connections with a higher ratio of the tensile strength to yield stress. Based on the results of finite element analysis including ductile damage simulation, this study reveals that the block shear strength of the lean duplex stainless steel specimens can be determined accurately using the mean between the shear yield stress and the shear ultimate stress. This paper also investigates the effect of stress triaxiality incorporated in the block shear equations found in the literature through comparative analysis with the bolted connection. The effect is shown to be negligible for the thin-walled lean duplex stainless steel welded connection, although higher stress triaxiality is developed in welded connection than in bolted connection. This paper recommends a block shear equation assuming the normal tensile stress in the net area in conjunction with partial shear strain hardening. The recommended equation was found to be more accurate than other equations for determining the block shear strength of the thin-walled lean duplex stainless steel welded connections.